Vascular Plug-Assisted Retrograde Transvenous Obliteration of Portosystemic Shunts for Refractory Hepatic Encephalopathy: A Case Report - Jonathan K. Park; Sung-Ki Cho; Stephen Kee; Edward W. Lee (Case Reports in Radiology)
While balloon-assisted retrograde transvenous obliteration (BRTO) has been used for two decades in Asia for the management of gastric variceal bleeding, it is still an emerging therapy elsewhere. Given the shunt closure brought about by the procedure, BRTO has also been used for the management of portosystemic encephalopathy with promising results. Modified versions of BRTO have been developed, including plug-assisted retrograde transvenous obliteration (PARTO), where a vascular plug is deployed within a portosystemic shunt. To our knowledge, we present the first North American case of PARTO in the setting of a large splenorenal shunt for the management of portosystemic encephalopathy.